Розвідки в районі Хмельницької АЕС - Кухарчук, Ю.В.; Романчук, О.М. (Археологічні дослідження в Україні, 2010)
In July, 2009, the Netishyn Group of the IA NASU conducted the searching and recognostic works near Khmelnytska nuclear power station. A series of Palaeolithic sites in outskirts of Bilotyn and Komyny villages of Izyaslav Region opened by O.M. Romanchuk in the 1990-s were studied and localized. One of them, Komny I, was researched by making a trench. A new Middle Palaeolithic site Bilotyn VI was discovered.